Isolated High Step-Up Soft-Switching Quasi-Z-Source DC–DC Converter - Guosheng Tian; Shuo Chen; Xinping Ding; Jishen Peng; Zhuangzhuang Kou (IEEE Access, 2024)
The DC microgrid with energy storage cells has strong stability, simple control, and a convenient power supply for DC loads, increasingly becoming the grid-connected structure of distributed generation systems. This paper presents an isolated high voltage gain soft-switching dc-dc converter suitable for DC microgrid applications. The converter comprises a dual-switch quasi-z-source network, multiplier voltage cell, and transformer. It has advantages such as high voltage gain, zero voltage switching (ZVS) of switches, zero voltage zero current switching (ZVZCS) turn-on and turn-off of diodes, and low input ripple current. The converter can achieve high voltage gain with an appropriate duty cycle and transformer turns ratio, reducing leakage inductance of transformer, which decreases the power loss and voltage spike of switch. Soft-switching of active devices increases the efficiency and decreases the output voltage ripples of the converter. The steady-state characteristics of the converter, voltage and current stress of components, the efficiency of the converter, and the selection of converter parameters are analyzed in detail. Finally, a 200 W experimental prototype is built in the laboratory for experimental verification, and the experimental results are consistent with the theoretical analysis.